Motifs des incendies de forêt en Algérie : analyse comparée des dires d'experts de la Protection Civile et des Forestiers par la méthode Delphi - Ouahiba Meddour-Sahar (Éditions en environnement VertigO, 2014)
The aim of this paper was to survey the perception of wildfire motifs by members of Civil Protection in Algeria. This survey complements a previous one, already accomplished by the same authors, but related to personnel of Forestry Service. It permitted an explanation of unknown causes, which in Algeria represent the large majority of fire starts. Understanding the reasons why fires start is a crucial factor in reducing their incidence through specific fire prevention campaigns. Survey was accomplished in three highly fire-prone wilayas (provinces) in North-Central Algeria by the Delphi method, based on opinions of an experts’ panel. Research has involved a total of 371 agents of Civil Protection Department, contacted by mail, telephone or directly, to whom a questionnaire ad hoc was submitted. Delphi identified anthropogenic activities as a major cause of fires, excluding natural causes. For involuntary events experts pointed out negligent disposal of cigarettes in more than 90 % of their replies, negligent stubble burning (82.97 %) and children games (65.30 %). For voluntary fires, results highlight fires from illegal dumping and burning of garbage (85.49 %) and the renewal of ranges by pastors (65.93 %). For accidental fires, experts referred to glass refraction/magnification (79.18 %), and power lines (70.66 %). Results reflect the activity of experts, whose perception of wildfires is influenced by their experience, knowledge and culture.